Effect of Organic Modification on the Compatibilization Efficiency of Clay in an Immiscible Polymer Blend - Sinha Ray, Suprakas; Bousmina, Mosto (Macromolecular rapid communications., 2005)
This communication describes the effect of organic modifier miscibility with the matrices, and the effect of the initial interlayer spacing of the organoclay, on the overall morphology and properties of an immiscible polycarbonate/poly(methyl methacrylate) blend. By varying the organic‐modifier‐specific interactions with the blend matrices at the same time as changing the initial interlayer spacing of the organoclay, different levels of compatibilization were revealed. The evidence for the interfacial compatibilization of the organoclay was assessed by scanning electron microscopy observations and was supported by differential scanning calorimetry analyses. The effect on the level of clay exfoliation was also examined. Differential scanning calorimetry scans of virgin, montmorillonite, and various organically modified montmorillonite‐compatibilized 40PC/60PMMA blends